Identification and Characterization of Arthrobacter nicotinovorans JI39, a Novel Plant Growth-Promoting Rhizobacteria Strain From Panax ginseng - Jiang, Yun; Song, Yu; Jiang, Chengyang; Li, Xiang; Liu, Tingting; Wang, Jiarui; Chen, Changqing; Gao, Jie (Frontiers in Plant Science, 2022)
A bacterial strain JI39 that had plant growth-promoting traits was isolated from the rhizosphere soil of Panax ginseng. The strain JI39 had the ability to produce high indole-3-acetic acid (13.1µg/mL), phosphate solubilization (164.2µg/mL), and potassium solubilization (16.1µg/mL), and nitrogen fixation. The strain JI39 was characterized to be Arthrobacter nicotinovorans based on morphological, physiological and biochemical traits, and through 16S rDNA sequence analysis. The optimal culture environment for JI39 growth was 1.0% NaCl, 30 ℃, pH 6.0, and without UV irradiation. The strain can produce cellulase and protease. The strain JI39 can significantly promote the growth of ginseng. After ginseng seeds were treated by 3×108 CFU/mL of JI39 bacterial suspension, the shoot’s length was significantly increased by 64.61% after 15 days. Meanwhile, the fresh weight of 2-year-old ginseng roots was significantly increased by 24.70% with treatment by the 108 CFU/mL bacterial suspension after 150 days in the field. The gene expression of phenylalanine ammonia-lyase, β-1.3 glucanase, chitinase, superoxide dismutase and peroxidase of ginseng was up regulated, and it also can improve the soil urease, phosphatase, invertase, and catalase activity. In conclusion, the bacterial strain JI39 could efficiently promote the growth of ginseng and has the potential to be a good microbial fertilizer for ginseng.